Realizing a hybrid competitive strategy and achieving superior export performance: A multiple case study of small and medium-sized Chinese owned Bordeaux vineyards when exporting to China - Jin, Misi (My University, 2019)
Based on literature review, this study identifies six factors, specifically, equipment and labour input in production, diverse expertise, supply chain structure, terroir, wine touristic attractiveness and information acquisition capabilities relate to realization of export competitive strategies for small and medium-sized Chinese-owned Bordeaux vineyards (SMCBV). A hybrid competitive strategy aims at obtaining superior export financial performance by emphasizing low-cost and high differentiation at the same time. This master’s thesis utilises a multiple case study to compare the export performance of a hybrid strategy with a single strategy as SMCBVs exporting wines to Chinese market. The empirical results reveal that a hybrid competitive strategy influences export performance of a SMCBV positively. In addition, the paper also finds that high-tech equipment input, diverse expertise and possession of capabilities relating to information acquisition are positively associated with the realization of a hybrid competitive strategy. Whereas, integrated supply chain contributes to cost-leadership competitive advantage. This study approaches new insights in wine marketing via hybrid competitive strategies, which enables existing SMCBVs or new entrants to improve their export performance in Chinese wine market.
Keywords: hybrid competitive strategy; small and medium-sized Chinese-owned Bordeaux vineyards; wine export; export performance; Chinese market; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|